Epigenetic Differences in Long Non-coding RNA Expression in Finnish and Russian Karelia Teenagers With Contrasting Risk of Allergy and Asthma - Ndika, Joseph; Karisola, Piia; Lahti, Vilma; Fyhrquist, Nanna; Laatikainen, Tiina; Haahtela, Tari; Alenius, Harri (Frontiers in Allergy, 2022)
Background: Previously, we investigated skin microbiota and blood cell gene expression in Finnish and Russian teenagers with contrasting incidence of allergic conditions. The microbiota and transcriptomic signatures were distinctly different, with high Acinetobacter abundance and suppression of genes regulating innate immune response in healthy subjects. Objective: Here, we investigated long non-coding RNA (lncRNA) expression profiles of blood mononuclear cells (PBMC) from healthy and allergic subjects, to identify lncRNAs that act at the interphase of microbiome-mediated immune homeostasis in allergy/asthma. Methods: Genome-wide co-expression network analyses of blood cell lncRNA/mRNA expression was integrated with skin microbiota profiles of Finnish (69) and Russian (75) subjects. Selected lncRNAs were validated by stimulation of cohort-derived PBMCs and a macrophage cell model with birch pollen allergen (Betv1) or lipopolysaccharide, respectively. Results: Finnish and Russian PBMCs were differentiated by 3818 lncRNA transcripts. In the Finnish subjects with high prevalence of allergy and asthma, a subset of 37 downregulated lncRNAs (including, FAM155A-IT1 and LOC400958) were identified. They were part of a co-expression network with 20 genes known to be related to asthma and allergic rhinitis (R > 0.95). Incidentally, all these 20 genes were also components of pathways corresponding to cellular response to bacterium. The Finnish and Russian samples were also differentiated by the abundance of 176 bacterial OTU (operational taxonomic units). The subset of 37 lncRNAs, associated with allergy, was most correlated with the abundance of Acinetobacter (R > +0.5), Jeotgalicoccus (R > +0.5), Corynebacterium (R < –0.5) and Micrococcus (R < –0.5). Conclusion: In Finnish and Russian teenagers with contrasting allergy and asthma prevalence, epigenetic differences in lncRNA expression appear to be important components of the underlying microbiota-immune interactions. Unravelling the functions of the 37 differing lncRNAs may be the key to understanding microbiome-immune crosstalk, and to develop clinically relevant biomarkers.